Aqueous two-phase separation enables selective purification of mono-PEGylated human serum albumin: influence of process parameters and reagent size - Alkanaimsh, Salem; Al-Rashed, Osama A.; Shaaban, Mohamed (Frontiers in Chemical Engineering, 2025)
PEGylation is widely used in biopharmaceuticals to enhance protein stability and half-life, but the resulting mixtures typically contain multiple PEGylated derivatives alongside unmodified proteins, complicating purification. In this study, we developed a novel aqueous two-phase separation (ATPS) strategy for selectively purifying mono-PEGylated human serum albumin (HSA). HSA was PEGylated using polyethylene glycol (PEG) reagents of different molecular weights (20 kDa and 40 kDa) and subsequently purified using ATPS. Our results demonstrated that ATPS effectively isolated PEGylated HSA with purity >99% and extremely high selectivity in the top phase. Tie-line length (TLL) significantly influenced yield and purity, whereas the volume ratio (Vr) had a minimal effect. Optimal conditions for the separation of 20 kDa PEGylated HSA were identified at a TLL of 29% (w/w) and a Vr of 2.5, achieving a yield of 50% and an equilibrium constant of 1.6. Under identical conditions, the yield and equilibrium constants for 40 kDa PEGylated HSA increased to 58% and 18, respectively, attributed to enhanced hydrophobic interactions from the larger PEG reagent. Furthermore, ATPS reached equilibrium rapidly within 30 min, resulting in high productivity levels of 1.3 and 1.5 g/L/h for 20 and 40 kDa PEGylated HSA, respectively. These findings illustrate the high efficiency and industrial potential of ATPS as an effective purification strategy for PEGylated therapeutic proteins.